THE ROLE OF EFFECTIVE LEADERSHIP IN ENHANCING FINANCIAL MANAGEMENT AND BUILDING ORGANIZATIONAL CONFIDENCE-AN EXPLORATORY STUDY IN HEALTH IN SALAH AL-DIN GOVERNORATE - Lecturer: Dured Musa Mahmoud (Scholars Digest Publishing, 2023)
The research aims to identify the role of effective leadership in enhancing financial management and building organizational confidence in the health of Salah al-Din. To achieve the objectives of the study, a questionnaire was distributed to a random sample of (130) workers in the health of Salah al-Din, and a number of results were reached, the most important of which is the existence of a positive relationship between effective leadership and financial management and the existence of the impact of financial management on organizational confidence at the level of morale 0.05 In light of these results, a set of recommendations were formulated, the most important of which are: The management of Salahuddin's health finances should be strengthened through the adoption of good practices and policies in money management, accounting and financial planning. Financial operations should be reviewed and necessary improvements made.
Keywords: effective leadership, financial management, organizational trust, Salahuddin Health.